Lipase Catalyzed Synthesis Of Aromatic Esters Of Sugar Alcohols - R. Croitoru; L. A. M. Van Den Broek; A. E. Frissen; C. M. Davidescu; F. Peter; C. G. Boeriu (Zenodo, 2011)
Commercially available lipases (Candida antarctica lipase B, Novozyme 435, Thermomyces lanuginosus lipase, and Lipozyme TL IM), as well as sol-gel immobilized lipases, have been screened for their ability to acylate regioselectively xylitol, sorbitol, and mannitol with a phenolic ester in a binary mixture of t-butanol and dimethylsulfoxide. HPLC and MALDI-TOF MS analysis revealed the exclusive formation of monoesters for all studied sugar alcohols. The lipases immobilized by the sol-gel entrapment method proved to be efficient catalysts, leading to high conversions (up to 60%) in the investigated acylation reactions. From a sequence of silane precursors with different nonhydrolyzable groups in their structure, the presence of octyl and i-butyl group was most beneficial for the catalytic activity of sol-gel entrapped lipases in the studied process. : {"references": ["H. Stamatis, V. Sereti, and F. N. Kolisis, \"Enzymatic synthesis of\nhydrophilic and hydrophobic derivatives of natural phenolic acids in\norganic media\", Journal of Molecular Catalysis B: Enzymatic, vol. 11,\npp. 323-328, 2001.", "C. Vafiadi, E. Topakas, K. K. Y. Wong, I. D. Suckling, and P.\nChristakopoulos, \"Mapping the hydrolytic and synthetic selectivity of a\ntype C feruloyl esterase (StFaeC) from Sporotrichum thermophile using\nalkyl ferulates\", Tetrahedron: Asymmetry, vol. 16, pp. 373-379, 2005.", "I. S. Yoo, S. J. Park, and H. H. Yoon, \" Enzymatic synthesis of sugar\nfatty acid esters\", J. Ind. Eng. Chem., vol. 13, no. 1, pp. 1-6, 2007.", "J. Piao, S. Adachi, \"Stability of O/W emulsions prepared using various\nmonoacyl sugar alcohols as an emulsifier\", Innovat. Food Sci. Emerg.\nTechnol., vol. 7, pp. 211-216, 2006.", "B. Guyot, B. Bosquette, M. Pina, and J. Graille, \"Esterification of\nphenolic acids from green coffee with an immobilized lipase from\nCandida antarctica in solvent-free medium \", Biotechnol. Let., vol. 19,\nno. 6, pp. 529-532, 1997.", "H. Stamatis, V. Sereti, and F. N. Kolisis, \"Studies on the enzymatic\nsynthesis of lipophilic derivatives of natural antioxidants\", JAOCS, vol.\n76, no. 12, pp. 1505-1510, 1999.", "A. M. B. Rahman, N. B. Chaibakhsh, M. A. B. Salleh, and R. N. Z. R. A.\nRahman, \" Application of artificial neural network for yield prediction\nof lipase-catalyzed synthesis of dioctyl adipate \", Appl. Biochem.\nBiotechnol., vol. 158, no. 3, pp. 722-735, 2009.", "F. Ganske, U. T. Bornscheuer, \"Optimization of lipase-catalyzed glucose\nfatty acid ester synthesis in a two-phase system containing ionic liquids\nand t-BuOH \", J. Mol. Catal. B: Enzym., vol. 36, pp. 40-42, 2005.", "J. Piao, S. Adachi, \"Enzymatic preparation of fatty acid esters of sugar\nalcohols by condensation in acetone using a packed-bed reactor with\nimmobilized Candida antarctica lipase\", Biocat. Biotrans., vol. 22, pp.\n269-274, 2004.\n[10] A. F. Artamanov, L. F. Burkovskaya, F. S. Nigmatullina, and B. Z.\nDzhiembaev, \"Synthesis of monoesters of d-sorbitol and aromatic\nacids\", Chem. Nat. Comp., vol. 33, no. 5, pp. 571-573, 1998.\n[11] F. Peter L. Poppe, C. Kiss, E. Szocs-B\u251c\u00a1ro, G. Preda, C. Zarcula, and A.\nOlteanu, \"Influence of precursors and additives on microbial lipases\nstabilized by sol-gel entrapment\", Biocat. Biotrans., vol. 23, pp. 251-\n260, 2005.\n[12] M. M. Bradford, \"A rapid and sensitive method for the quantitation of\nmicrogram quantities of protein utilizing the principle of protein-dye\nbinding\", Anal Biochem., vol. 72, pp. 248-254, 1976.\n[13] R. ter Haar, H. A. Schols, L. A. M. van den Broek, D. Sa\u2500\u0192lam, A. E.\nFrissen, C. G. Boeriu, and H. Gruppen, \"Molecular sieves provoke\nmultiple substitutions in the enzymatic synthesis of fructose\noligosaccharide-lauryl esters\", J. Mol. Catal. B: Enzymatic, vol. 62, pp.\n183-189, 2010.\n[14] C. Zarcula, C. Kiss, L. Cor\u251c\u00abci, R. Croitoru, C. Csunderlik, and F. Peter,\n\"Combined sol-gel entrapment and adsorption method to obtain solidphase\nlipase biocatalyts\", Rev. Chim.(Bucharest), vol. 60, no. 9, pp. 922-\n927, 2009.\n[15] C. Zarcula, R. Croitoru, L. Cor\u251c\u00abci, C. Csunderlik, and F. Peter,\n\"Improvement of lipase catalytic properties by immobilization in hybrid\nmatrices\", Int. J. Chem. Biomol. Eng., vol. 2, no. 3, pp. 138-143, 2009.\n[16] S. Naik, A. Basu, R. Saikia, Bhawna Madan, Pritish Paul, Robin\nChaterjee, Jesper Brask, and Allan Svendsen, \"Lipases for use in\nindustrial biocatalysis: Specificity of selected structural groups of\nlipases\", J. Mol. Catal. B: Enzymatic, vol. 65, pp. 18-23, 2010.\n[17] F. Peter, C. Zarcula, S. Kakasi-Zsurka, R. Croitoru, C. Davidescu, and C.\nCsunderlik, \"Solid-phase lipase biocatalysts for kinetic resolutions\", J.\nBiotechnol., 136S, S356-S401, 2008.\n[18] R. T. Otto, H. Scheib, U. T. Bornscheuer, J. Pleiss, C. Syldatk, and R.\nD. Schmid, \"Substrate specificity of lipase B from Candida antarctica in\nthe synthesis of arylaliphatic glycolipids\", J. Mol. Catalysis B:\nEnzymatic, vol. 8, pp. 201-211, 2000."]}